PENINGKATAN VISIBILITAS UMKM DENGAN MEMANFAATKAN TEKNOLOGI DIGITAL VIA GOOGLE MAPS DI DESA SAMPE RAYA KAB. LANGKAT - Suhardi Napid; Ahmad Bakhori; Abdul Haris Nasution; Mhd.Rafiq Yanhar; Rachmat Rizaldi; Amanda Arba'a (Jurnal Pengabdian Mitra Masyarakat, 2025)
This Community Service activity aims to increase the visibility and competitiveness of UMKM in Sampe Raya Village, Langkat Regency, through the use of specific digital technologies, namely Google Maps. The main challenges faced by village UMKM are limited market access and low visibility, as most of their businesses are not digitally registered, making them difficult to find by customers from outside the region or visitors.The method used is participatory training and implementation assistance, covering three main stages: Socialization and initial potential data collection; Technical training on creating Google Maps accounts, location verification, business description optimization, and digital product photography techniques; and Post-training assistance to ensure that UMKM can manage reviews and update information independently.The results of this activity showed a significant increase in the digital literacy of UMKM and the registration of 100% of UMKM involved in the Sampe Raya Village digital map. After the mentoring, the average impression (number of views) of their businesses on Google Maps increased, opening up new market potential from customers searching for products or services through digital navigation. The conclusion of this PkM is that the integration of free and easily accessible digital tools such as Google Maps is an effective and sustainable solution to empower village UMKM, integrate them into the digital economy, and support local economic growth.